Women’s viewpoints on egg freezing in Austria: an online Q-methodology study - Kostenzer, Johanna (BMC Med Ethics, 2021)
BACKGROUND: Egg freezing has emerged as a technology of assisted reproductive medicine that allows women to plan for the anticipated loss of fertility and hence to preserve the option to conceive with their own eggs. The technology is surrounded by value-conflicts and is subject to ongoing discussions. This study aims at contributing to the empirical-ethical debate by exploring women’s viewpoints on egg freezing in Austria, where egg freezing for social reasons is currently not allowed. METHODS: Q-methodology was used to identify prevailing viewpoints on egg freezing. 46 female participants ranked a set of 40 statements onto a 9-column forced choice ranking grid according to the level of agreement. Participants were asked to explain their ranking in a follow-up survey. By-person factor analysis was used to identify distinct viewpoints which were interpreted using both the quantitative and the qualitative data. RESULTS: Three distinct viewpoints were identified: (1) “women should decide for themselves”, (2) “we should accept nature but change policy”, and (3) “we need an informed societal debate”. These viewpoints provide insights into how biomedical innovations such as egg freezing are perceived by women in Austria and illustrate the normative tensions regarding such innovations. CONCLUSIONS: Acknowledging the different prioritizations of values regarding assisted reproductive technologies is important to better understand the underlying normative tensions in a country where egg freezing for social reasons is currently not allowed. The study adds new empirical insights to the ongoing debate by outlining and discussing viewpoints of those directly affected: women. Following up on the lay persons perspective is particularly important in the context of future biomedical innovations that may challenge established norms and create new tensions. It therefore also adds to the societal debate and supports evidence-informed policy making in that regard.